2012
DOI: 10.1371/journal.pone.0038990
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Karyopherin α1 and α7 Interacting Proteins in Porcine Tissue

Abstract: Specialized trafficking systems in eukaryotic cells serve a critical role in partitioning intracellular proteins between the nucleus and cytoplasm. Cytoplasmic proteins (including chromatin remodeling enzymes and transcription factors) must gain access to the nucleus to exert their functions to properly program fundamental cellular events ranging from cell cycle progression to gene transcription. Knowing that nuclear import mediated by members of the karyopherin α family of transport receptors plays a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Bacterially produced recombinant importin α8 exhibited strong binding to importin β1, consistent with previous reports [15][16][17]. In addition, we demonstrated that importin α8 interacted with the SV40TNLS substrate and transported it to the nucleus.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Bacterially produced recombinant importin α8 exhibited strong binding to importin β1, consistent with previous reports [15][16][17]. In addition, we demonstrated that importin α8 interacted with the SV40TNLS substrate and transported it to the nucleus.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports indicated that importin α8 only binds weakly, or not at all, to the SV40TNLS [16][17][18]. However, amino acid sequence alignment of importin α8 and importin α1 revealed that the critical amino acids in the major and minor NLS-binding sites are conserved ( Fig.…”
Section: Importin α8 Transports Cnls Substrates Into the Nucleusmentioning
confidence: 87%
See 2 more Smart Citations
“…Screening synthetic libraries, such as in vitro virus libraries (18) and oriented peptide libraries (19), is effective for identifying amino acid sequences that bind to Imp-␣ and act as cNLSs, but these methods do not identify native cargoes. The identification of native Imp-␣ cargoes was performed using Far Western-based cellular proteomic approaches (20), yeast two-hybrid screening (21), GST pulldown assays (22,23), and co-immunoprecipitation techniques (24). These methods depend on the protein-protein interaction between Imp-␣ and its cargo.…”
mentioning
confidence: 99%